2019
DOI: 10.3889/oamjms.2019.336
|View full text |Cite
|
Sign up to set email alerts
|

Value of Combination of Standard Axial and Thin-Section Coronal Diffusion-weighted Imaging in Diagnosis of Acute Brainstem Infarction

Abstract: AIM: To determine the value of the combination of thin-section 3 mm ‎coronal and standard ‎axial DWI and their impact in facilitating the diagnosis of ‎‎acute brainstem infarction. METHODS: A cross-sectional study conducted from the 1st of April 2017 to the end of February 2018 on 100 consecutive patients (66% were male, and 34% were female) with isolated acute ischemic infarction in the ‎brainstem. The abnormal MRI findings concerning the ischemic lesions were interpreted on standard axial 5 mm and thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Diffusion-weighted imaging (DWI) has high sensitivity and specificity in detecting ischemic lesions, and it can facilitate diagnosis and provide important information associated with prognosis for brainstem infarction [11]. In previous imaging studies, the number and distribution of DWI lesions have been shown to offer vital clues to the underlying stroke mechanisms and prognosis of patients with infratentorial strokes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) has high sensitivity and specificity in detecting ischemic lesions, and it can facilitate diagnosis and provide important information associated with prognosis for brainstem infarction [11]. In previous imaging studies, the number and distribution of DWI lesions have been shown to offer vital clues to the underlying stroke mechanisms and prognosis of patients with infratentorial strokes [12,13].…”
Section: Introductionmentioning
confidence: 99%